Identification and Expression Patterns of Putative Diversified Carboxylesterases in the Tea Geometrid Ectropis obliqua Prout - Sun, Liang; Wang, Qian; Wang, Qi; Zhang, Yuxing; Tang, Meijun; Guo, Huawei; Fu, Jianyu; Xiao, Qiang; Zhang, Yanan; Zhang, Yongjun (Frontiers in Physiology, 2017)
Carboxylesterases (CXEs) belong to a family of metabolic enzymes. Some CXEs act as odorant-degrading enzymes (ODEs), which are reportedly highly expressed in insect olfactory organs and participate in the rapid deactivation of ester pheromone components and plant volatiles. The tea geometrid Ectropis obliqua Prout produces sex pheromones consisting of non-ester functional compounds but relies heavily on acetic ester plant volatiles to search for host plants and locate oviposition sites. However, studies characterizing putative candidate ODEs in this important tea plant pest are still relatively scarce. In the present study, we identified 35 candidate EoblCXE genes from E. obliqua chemosensory organs based on previously obtained transcriptomic data. The deduced amino acid sequences possessed the typical characteristics of the insect CXE family, including oxyanion hole residues, the Ser-Glu-His catalytic triad, and the Ser active included in the conserved pentapeptide characteristic of esterases, Gly-X-Ser-X-Gly. Phylogenetic analyses revealed that the EoblCXEs were diverse, belonging to several different insect esterase clades. Tissue- and sex-related expression patterns were studied via reverse-transcription and quantitative real-time polymerase chain reaction analyses (RT- and qRT-PCR). The results showed that 35 EoblCXE genes presented a diversified expression profile; among these,12 EoblCXEs appeared to be antenna-biased, two EoblCXEs were non-chemosensory organ-biased, 12 EoblCXEs were ubiquitous, and nine EoblCXEs showed heterogeneous expression levels among different tissues. Intriguingly, two EoblCXE genes, EoblCXE7 and EoblCXE13, were not only strongly localized to antennal sensilla tuned to odorants, such as the sensilla trichodea (Str I and II) and sensilla basiconica (Sba), but were also expressed in the putative gustatory sensilla styloconica (Sst), indicating that these two CXEs might play multiple physiological roles in the E. obliqua chemosensory processing system. This study provides the first elucidation of CXEs in the chemosensory system of a geometrid moth species and will enable a more comprehensive understanding of the functions of insect CXEs across lepidopteran species.